Geophysical study of land subsidence: example from Pokhara basin - Yoshida, M.; Pant, S. R.; Adhikary, P. C.; Dangol, V.; Shrestha, S. (Journal of Nepal Geological Society, 2006)
Land subsidence is a serious problem in the Pokhara city and surrounding wide areas consisting of recent debris flow deposits. Owing to their calcareous matrix the debris flow deposits are more-or-less well cemented, even though their age ranges just from 12,000 to 700 years BP. There are numerous caves and caverns in these deposits. To investigate the danger of subsidence, ground penetrating radar and electrical resistivity tomography were employed to detect and map the caves and caverns. The results are quite encouraging and the above methods are found to be quite effective in formulating the control measures to the land subsidence hazard.